A Unique Case of Disseminated Tubercular Lymphadenitis with Recurrent Waxing-Waning Course - Shuvajit Roy; Rakhi Sanyal (Journal of Clinical and Diagnostic Research)
Extrapulmonary Tuberculosis (EPTB) is particularly challenging to diagnose and manage due to the wide range of presentations. A 52-year-old male Human Immunodeficiency Virus (HIV)-negative immunocompetent patient presented with recurrent symptoms of low-grade fever, severe weight loss, and anorexia over several years following a recurrent waxing-waning course. The initial clinical examination was non significant. Biochemical investigations were also non conclusive except for a chronic inflammatory state as C-reactive Protein (CRP) levels remain constantly raised throughout the period. Microbiological investigations like sputum for Acid Fast Bacillus (AFB) and GeneXpart were negative for Tuberculosis (TB) but the tuberculin test came as positive. Radiological imaging including Contrast-Enhanced Computed Tomography (CECT) abdomen and Positron Emission Tomography-computed Tomography (PET-CT) revealed conglomerated, metabolically active lymphadenopathy in the abdomen, mediastinum, and neck. Subsequent clinical examination revealed palpable lymphadenopathy in the neck. Histopathological examination of the dissected left supraclavicular lymph node confirmed tubercular lymphadenitis. Incidentally, Upper Gastrointestinal (GI) endoscopy showed fundal ulcers which were positive for rapid urease test. The patient was put on first-line anti-tubercular therapy for EPTB and H. Pylori triple regimen for fundal ulcer. The patient showed significant improvement on follow-up.